Association of future cancer metastases with fibroblast activation protein-α: a systematic review and meta-analysis - Janani, Majid; Poorkhani, Amirhoushang; Amiriani, Taghi; Donyadideh, Ghazaleh; Ahmadi, Farahnazsadat; Jorjanisorkhankalateh, Yalda; Beheshti-Nia, Fereshteh; Kalaei, Zahra; Roudbaraki, Morad; Soltani, Mahsa; Khori, Vahid; Alizadeh, Ali Mohammad (Frontiers in Oncology, 2024)
Introduction Fibroblast activation protein-α (FAP-α) is a vital surface marker of cancer-associated fibroblasts, and its high expression is associated with a higher tumor grade and metastasis. A systematic review and a meta-analysis were performed to associate future metastasis with FAP-α expression in cancer. Methods In our meta-analysis, relevant studies published before 20 February 2024 were systematically searched through online databases that included PubMed, Scopus, and Web of Science. The association between FAP-α expression and metastasis, including distant metastasis, lymph node metastasis, blood vessel invasion, vascular invasion, and neural invasion, was evaluated. A pooled odds ratio (OR) with 95% confidence intervals (CI) was reported as the measure of association. Results A total of 28meta-analysis. The random-effects model for five parameters showed that a high FAP-α expression was associated with blood vessel invasion (OR: 3.04, 95% CI: 1.54–5.99, I2 = 63%, P = 0.001), lymphovascular invasion (OR: 3.56, 95% CI: 2.14–5.93, I2 = 0.00%, P < 0.001), lymph node metastasis (OR: 2.73, 95% CI: 1.96–3.81, I2 = 65%, P < 0.001), and distant metastasis (OR: 2.59; 95% CI: 1.16–5.79, I2 = 81%, P < 0.001). However, our analysis showed no statistically significant association between high FAP-α expression and neural invasion (OR: 1.57, 95% CI: 0.84–2.93, I2 = 38%, P = 0.161). Conclusions This meta-analysis indicated that cancer cells with a high FAP-α expression have a higher risk of metastasis than those with a low FAP-α expression. These findings support the potential importance of FAP-α as a biomarker for cancer metastasis prediction.